Multi-Observatory Research of Young Stellar Energetic Flares (MORYSEF): X-Ray-flare-related Phenomena and Multi-epoch Behavior - Getman, Konstantin V.; Feigelson, Eric D.; Waggoner, Abygail R.; Cleeves, L. Ilsedore; Forbrich, Jan; Ninan, Joe P.; Kochukhov, Oleg; Airapetian, Vladimir S.; Dzib, Sergio A.; Law, Charles J.; Rab, Christian (The Astrophysical journal, 2024)
The most powerful stellar flares driven by magnetic energy occur during the early pre-main-sequence (PMS) phase. The Orion Nebula represents the nearest region populated by young stars, showing the greatest number of flares accessible to a single pointing of Chandra. This study is part of a multi-observatory project to explore stellar surface magnetic fields (with the Hobby–Eberly Telescope Habitable-zone Planet Finder, HET-HPF), particle ejections (with the Very Long Baseline Array, VLBA), and disk ionization (with the Atacama Large Millimeter/submillimeter Array, ALMA) immediately following the detection of PMS superflares with Chandra. In 2023 December, we successfully conducted such a multi-telescope campaign. Additionally, by analyzing Chandra data from 2003, 2012, and 2016, we examine the multi-epoch behavior of PMS X-ray emission related to PMS magnetic cyclic activity and ubiquitous versus sample-confined megaflaring. Our findings are as follows. (1) We report detailed stellar quiescent and flare X-ray properties for numerous HET/ALMA/VLBA targets, facilitating ongoing multiwavelength analyses. (2) For numerous moderately energetic flares, we report correlations (or lack thereof) between flare energies and stellar mass/size (presence/absence of disks) for the first time. The former is attributed to the correlation between convection-driven dynamo and stellar volume, while the latter suggests the operation of solar-type flare mechanisms in PMS stars. (3) We find that most PMS stars exhibit minor long-term baseline variations, indicating the absence of intrinsic magnetic dynamo cycles or observational mitigation of cycles by saturated PMS X-rays. (4) We conclude that X-ray megaflares are ubiquitous phenomena in PMS stars, which suggests that all protoplanetary disks and nascent planets are subject to violent high-energy emission and particle irradiation events.